Prognostic Role of Immune Cells in Hepatitis B-associated Hepatocellular Carcinoma Following Surgical Resection Depends on Their Localization and Tumor Size. Issue 1 (January 2016) - Wang, Qin; Luan, Wei; Warren, Leslie; Fiel, M. Isabel; Blank, Sima; Kadri, Hena; Mandeli, John; Hiotis, Spiros P.
Abstract : This study aims to evaluate localized expression of CD4, interleukin (IL)-17, Foxp3, and CD8 in hepatitis B-associated hepatocellular carcinoma (HBV-HCC) and to explore their potential effects on outcome following surgical resection. This prospective study includes 66 HBV-HCC surgical resection patients enrolled from 2008 to 2013. CD4, IL-17, Foxp3, and CD8 mRNA in 4 regions of the resection specimens (center of the tumor, periphery of the tumor, non-neoplastic liver bordering tumor, non-neoplastic liver distant from tumor) was quantitated using real-time polymerase chain reaction. The tumoral regions had lower CD4 and CD8 expression as compared with paired non-neoplastic regions, whereas the expression of IL-17 and Foxp3 did not differ. High Foxp3 in all regions except non-neoplastic liver distant from tumor was associated with poor overall survival, whereas low CD8 expression in distant non-neoplastic liver may be associated with high HCC recurrence rate. Although the expression of almost all molecules did not differ between small (⩽3 cm) and large HCC (>3 cm), high IL-17 in periphery of tumor, high CD8 in center of tumor, or low CD8 in distant non-neoplastic liver was associated with high HCC recurrence rate in patients with small HCC, but not in those with large HCC. The effect of immune cells on HCC progression therefore depends on the expression level, localization, and tumor size, and an imbalance toward regulatory T cells is associated with poor outcome. Abstract : Supplemental Digital Content is available in the text.